A Study of Style and Stylistics in Farley Mowat's People of the Deer - Denish Durai; G Baskaran; Evan Afri (International Journal of English and Applied Linguistics (IJEAL), 2021)
The article attempts to evaluate Farley Mowat's People of the Deer in terms of style and stylistic perspectives. Mowat (1921- 2014) is a well-known Canadian author. In the usage of the language resource, he has exhibited an excellent degree of competency. His styles of writing were an autobiographical fashion. With regard to linguistic and literary styles, the study examined style and stylistic trends. The researcher suggests that the study would be helpful for the students of linguistics and literature in the future. This study will not provide a detailed description of all stylistic devices; rather, it will provide a picture of the traditional flouted as well as variations that Mowat has introduced. Style, Stylistics, Alliteration, Repetition, Collocation, and so on are all examples of major literary and linguistic stylistics.